Cultural factors in depressive experience and its severity: A case report - C. Regueiro Martín-Albo; F. Mayor Sanabria; E. Expósito Durán; M. Fernández Fariña; M. Navas Tejedor (European Psychiatry, 2023)
Introduction For a very long time, anthropologists and psychiatrists have studied how the symptomatology of mental diseases varies among cultures. Different social environments approach depression in different ways, and cultural practices and meanings influence how it develops. Culture also affects how symptoms are felt and described, how treatments are chosen, how patients and doctors interact, how likely it is that certain events, like suicide, will occur, and how professionals behave. As a result, all of these circumstances must be taken into consideration when approaching the diagnosis and management of depressive disorders. To illustrate the above, we present the case of a 31-year-old man, originally from Nigeria, who was admitted to the hospital after a suicide attempt by precipitation onto the subway tracks. Objectives (1) To describe the clinical particularities of this case, focusing on the diagnostic difficulties we faced derived from intercultural contrasts (2) To review cross-cultural differences in the symptomatology and its implication on severity of depressive disorders. Methods